Dynamic general equilibrium modelling for forecasting and policy a practical guide and documentation of MONASH - Dixon, Peter B.; Rimmer, Maureen T. (Elsevier, 2002)
The Contributions to Economic Analysis series consists of a number of previously unpublished studies. The term economic analysis is used because it covers the activities of the theoretical economist and the research worker.
Keywords: Economics -- Mathematical models.; Equilibrium (Economics) -- Mathematical models.; Statics and dynamics (Social sciences) -- Mathematical models.; Economic forecasting -- Mathematical models.; Economic policy -- Mathematical models.; Business & Economics -- Economics -- Microeconomics.; Business & Economics -- Economics -- General.; Econometrics.; Economic forecasting.; elektronické knihy; electronic books